The use of the electrical stimulation device for the muscles in the limit determines the elbow joint during the lifting of the disabled weightlifting players - Al-Ibraheemi, D. H. E.; Alhasan, A. M. A.; Abdulameer, F. I. (Journal of Human Sport & Exercise, 2019)
Neuromuscular Electrical Simulation has been improved as the novel therapeutic alternative for the patients who affected with muscle impairment. It has proven significant improvement in strengthening the physical condition and the functional capacity of the patients. In this research work incorporation of Neuromuscular Electrical Simulation for the muscles in the limit determines the elbow joint during the lifting of the disabled weightlifting players. While the weights are lifting by the players without proper cautiousness and concentration the tendon and associated flexor or pronator muscles may get affected and leads to severe pain and causes disability to perform the weightlifting practice. In the process of reviving the weight lifting players different methods are used. The research study focuses on the use of electrical stimulator devices for improving the muscle strength and healing of the elbow joint injuries.